Medium-scale experiments on vented hydrogen deflagration. (July 2015) - Kuznetsov, Mike; Friedrich, Andreas; Stern, Gerold; Kotchourko, Natalie; Jallais, Simon; L'Hostis, Beatrice
Abstract: A series of medium-scale experiments on vented hydrogen deflagration was carried out at the KIT test side in a chamber of 1 × 1 × 1 m 3 size with different vent areas. The experimental program was divided in three series: (1) uniform hydrogen–air mixtures; (2) stratified hydrogen–air mixtures within the enclosure; (3) a layer deflagration of uniform mixture. Different uniform hydrogen–air mixtures from 7 to 18% hydrogen were tested with variable vent areas 0.01–1.0 m 2 . One test was done for rich mixture with 50% H2 . To vary a gradient of concentration, all the experiments with a stratified hydrogen–air mixtures had about 4%H2 at the bottom and 10 to 25% H2 at the top of the enclosure. Measurement system consisted of a set of pressure sensors and thermocouples inside and outside the enclosure. Four cameras combined with a schlieren system (BOS) for visual observation of combustion process through transparent sidewalls were used. Four experiments were selected as benchmark experiments to compare them with four times larger scale FM Global tests (Bauwens et al., 2011 ) and to provide experimental data for further CFD modelling. The nature of external explosion leading to the multiple pressure peak structure was investigated in details. Current work addresses knowledge gaps regarding indoor hydrogen accumulations and vented deflagrations. The experiments carried out within this work attend to contribute the data for improved criteria for hydrogen–air mixture and enclosure parameters to avoid unacceptable explosion overpressure. Based on theoretical analysis and current experimental data a further vent sizing technology for hydrogen deflagrations in confined spaces should be developed, taking into account the peculiarities of hydrogen–air mixture deflagrations in presence of obstacles, concentration gradients of hydrogen–air mixtures, dimensions of a layer of flammable cloud, vent inertia, etc. Graphical abstract: Highlights: A series of experiments on vented hydrogen deflagration was carried out in a chamber of 1 × 1 × 1 m 3 size. UniformH2 –air mixtures from 7 to 18% H2 and stratified mixtures up to 25% H2 were tested with variable vents. An effect of uniform and stratified mixture reactivity on maximum combustion pressure was studied. A nature of external explosion leading to multiple pressure peak structure was investigated in details.